The impact of software updates on accuracy of intraoral scanners - Judit Schmalzl; Ivett Róth; Judit Borbély; Péter Hermann; Bálint Vecsei (BMC, 2023)
Abstract Background Digital workflow is showing an increasing tendency in everyday dentistry. Accuracy is essential during digital dental workflows for all indication areas. The present study aimed to evaluate the effect of software updates on the accuracy of intraoral scanner (IOS) devices. Methods 3Shape Trios 3 Pod with software versions 18.1.2. (TRI3_1) and 20.1.2. (TRI3_2); 3Shape Trios 4 Move, version 19.2.2. (TRI4_1); and 3Shape Trios 4 Pod, version 20.1.1. (TRI4_2) were used to take direct optical impressions from a polymethyl methacrylate (PMMA) full arch reference model with prepared teeth (FDI 11,14,17 for crowns and FDI 26 for onlay) and an edentulous region (between FDI 14 and 17). The scanners were used eight times; STL files were imported into Geomagic Control X for accuracy assessment by comparing them to a reference data set created by an industrial high-precision scanner (AICON SmartScan-3D C5). The average deviation of the surface points was calculated in three locations: across a full arch (Parameter 1), the region of a four-unit bridge (Parameter 2), and a single prepared abutment (Parameter 3). Results In parameter 1 and 2, the newest model with the latest software (TRI4_2) reached the highest accuracy (31.06 ± 5.24 µm and 21.69 ± 7.50 µm). In parameter 3, an older generation scanner running legacy software produced the highest accuracy: TRI4_1, 11.75 ± 0.35 µm. Conclusion Appropriate software updates can significantly increase the trueness and precision of intraoral scanner devices. With updated software, the older generation can match the accuracy level of latest equipment.